2019
DOI: 10.12783/dtetr/ecae2018/27724
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss via Wavelet Entropy and Particle Swarm Optimized Trained Support Vector Machine

Abstract: This paper proposed a method that combines wavelet entropy with particle swarm optimized support vector machine to detect hearing loss (HL). The dataset for this task contains 75 images: 25 healthy controls, 25 left-sided hearing loss patients, and 25 right-sided hearing loss patients. The results shows that our method has higher accuracy than some traditional method. The sensitivities over healthy control, left-sided HL patients, and right-sided HL patients are 85.20± 3.79, 85.20± 4.64, and, 86.40± 5.06, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Their earlier application of genetic algorithm for hearing loss detection system provides ideas for many subsequent researchers. Fang-zhou BAO (2018) et al [11] In the process of referring to previous studies, we found there are common problems in defecting hearing loss:…”
Section: Introductionmentioning
confidence: 68%
“…Their earlier application of genetic algorithm for hearing loss detection system provides ideas for many subsequent researchers. Fang-zhou BAO (2018) et al [11] In the process of referring to previous studies, we found there are common problems in defecting hearing loss:…”
Section: Introductionmentioning
confidence: 68%